2018
DOI: 10.1177/0009922818806315
|View full text |Cite
|
Sign up to set email alerts
|

Injury Prevention Education in the Waiting Room of an Underserved Pediatric Primary Care Clinic

Abstract: Unintentional injuries are the leading cause of childhood mortality in the United States. Study aims included educating families about injury prevention and improving satisfaction with the waiting room experience. Two hundred caregivers with young children in the waiting room of an underserved pediatric primary care clinic participated in brief individual education sessions and received a toolkit containing small safety items and content highlighting age-appropriate safety topics. Participants completed 2 foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
9
0
4
Order By: Relevance
“…The areas of childhood injuries prevention topic covered by the studies selected mostly include home injuries such as fall, burns and poisoning (12,(14)(15)(16). Outdoor injuries such as drowning, road safety, animal safety are also mentioned in some of the studies (9,13,17), and one study mention violence (intentional) injuries prevention in their health education intervention (6).…”
Section: Features Of the Intervention Methods Of Deliveriesmentioning
confidence: 99%
See 3 more Smart Citations
“…The areas of childhood injuries prevention topic covered by the studies selected mostly include home injuries such as fall, burns and poisoning (12,(14)(15)(16). Outdoor injuries such as drowning, road safety, animal safety are also mentioned in some of the studies (9,13,17), and one study mention violence (intentional) injuries prevention in their health education intervention (6).…”
Section: Features Of the Intervention Methods Of Deliveriesmentioning
confidence: 99%
“…From there on, 34 articles were reviewed in full article text and further 26 paper were being excluded as there were no description on the health education intervention delivery methods in detail and remaining studies setting were only mentioned in full text that it was done outside primary care setting. Therefore, the final paper included in this review was 8 papers (6,9,(12)(13)(14)(15)(16)(17). Summary of the results are presented in the PRISMA flow chart in the…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study authors concluded there is significant value in the provision and use of safety products (Phelan et al, 2011). Yet recent data from a pediatric clinic suggest even freely-distributed safety items are not always used at home (Habermehl et al, 2019). Identifying "most used" items and focusing on the distribution of these higher-yield items in the future could increase the odds that families use the items they receive from a safety center or MSC.…”
Section: Introductionmentioning
confidence: 99%